Balance sheets and the lending banker : a new assessment of accounts an d their interpretation in relation to bank advances - Clemens, J. H. (London: Europa, 1961)
The book has been planned primarily as a study of balance sheets, from the special point of view of the banker. The emphasis is therefore upon accounts rather than upon bank lending.
Includes bibliographical footnotes and index.
hza 30/08/2018
Loans
Keywords: Bank credit; Financial statements